Enhancing R control chart performance in monitoring process dispersion using scaled weighted variance method for skewed populations - Atta, Abd; Shoraim, Majed; Syed Yahaya, Sharipah Soaad; Abuzaid, Ali; Mahdi, Esam (Medwell Publishing, 2020)
This study improves the performance of R control chart for monitoring process dispersion of skewed populations using scaled weighted variance method. This control chart, called Scaled Weighted Variance R control chart (SWV-R) hereafter, the SWV-R control chart compared with Skewness Correction R chart (SC-R) and Weighted Variance R chart (WV-R) in terms of false alarm. In terms of probability of detection rates the proposed SWV-R chart is compared with R chart of the exact method, SC-R and WV-R control charts. The proposed SWV-R control chart reduces to the Shewhart R control chart when the underlying distribution is symmetric. An illustrative example is given to show how the proposed SWV-R control chart is constructed and works simulations study show that the proposed SWV-R control chart has the lower false alarm rates than the SC-R and WV-R control charts, when the underlying distributions are Weibull and gamma. In terms of the probability of detection rates, the proposed SWV-R control chart is closer to R control chart with the exact method than WV-R and almost the same performance as SC-R chart.